Hubungan Kompetensi Dan Kualitas Pelayanan Dengan Tingkat Kepuasan Masyarakat Pengguna Layanan Administrasi Kependudukan - Karningsih Karningsih (Universitas 17 Agustus 1945 Semarang, 2023)
The government is a bureaucratic organization in public service, so the government bureaucratic organization is the leading organization related to public service. In terms of including government institutions as a locus of research is the Office of Population and Civil Registration, providing services regarding population administration, the most important thing is how to provide assistance and convenience to the community in order to fulfill their needs and interests, especially birth certificates. A quality service provided to the community demands there is an effort from all employees who have competence, because any task carried out by each employee contains an element of service which in turn will affect the quality of services or products from the agency where the employee works which is accepted by the community, and community satisfaction using population services in the form of a certificate birth. The results of the hypothesis test showed a significant relationship between competence and quality of service, with the satisfaction of the people who use population administration services.